Metformin Promotes Axonal Regeneration and Functional Recovery in Diabetic Rat Model of Sciatic Nerve Transection Injury - Junxiong Ma; Jun Liu; Yu Chen; Hailong Yu; Liangbi Xiang (NeuroSci, 2022)
In our previous study, metformin was able to promote nerve regeneration after sciatic nerve crushing in rats under diabetic conditions. However, a crush injury also has a strong ability to spontaneously recover. Therefore, in our present study, a model of transection injury of the sciatic nerve in diabetic rats was utilized to detect whether metformin could still promote nerve regeneration. Diabetes was induced via an injection of 50 mg/kg of streptozotocin in rats. After transection injury of the sciatic nerve, the rats were randomly divided into a high-dose metformin group (500 mg/kg/d), mid-dose metformin group (200 mg/kg/d), low-dose metformin group (30 mg/kg/d) and control group (normal saline). The metformin or normal saline was intraperitoneally injected for 4 weeks. Then, behavioral, electrophysiological and morphometric analyses were performed. The results showed that metformin could significantly promote functional restoration and axonal regeneration of the sciatic nerve after transection injury under diabetic conditions. Furthermore, high doses and middle doses of metformin presented more of this ability than a low dose of metformin. In conclusion, metformin is able to accelerate sciatic nerve repair after transection injury under diabetic conditions, showing the therapeutic potential of metformin in the management of nerve injuries during diabetes mellitus.